2020
DOI: 10.3390/molecules25051024
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of the Polysaccharide Precursor, D-Isofloridoside, from Laurencia undulata on Alcohol-Induced Hepatotoxicity in HepG2 Cells

Abstract: Alcoholic liver disease (ALD) threatens human health, so it is imperative that we find ways to prevent or treat it. In recent years, the study of polysaccharides has shown that they have different kinds of bioactivities. Among them are many biological effects that have been attributed to polysaccharide precursors. D-Isofloridoside (DIF) is one of the polysaccharide precursors from the marine red alga Laurencia undulata. This study evaluated the effect of DIF on alcohol-induced oxidative stress in human hepatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…DIF purified from Laurencia undulata , and demonstrated that it has antioxidant and metal matrix protease inhibitory activity in our previous study. , DIF: 1 H NMR (400 MHz, DMSO- d 6 ) δ H 3.47 (6H, m, H-1′,H-3′, H-6), 3.76 (1H, t, J = 2.6 Hz, H-5), 3.69 (1H, brs, H-2), 3.51 (2H, m, H-3, H-4), 3.41 (1H, m, H-2′), 4.35 (1H, m, HO-2), 4.47 (1H, m, HO-2′), 4.81 (1H, d, J = 2.6 Hz, H-1), 4.56 (1H, m, HO-4), 4.58 (1H, m, HO-6), 4.44 (1H, m, HO-1′), 4.38 (1H, m, HO-3); 13 C NMR (100 MHz, DMSO- d 6 ) δ C 68.9 (C-4), 60.6 (C-1′), 80.6 (C-2′), 71.3 (C-5), 99.4 (C-1), 69.7 (C-3), 61.0 (C-6), 60.8 (C-3′), 68.8 (C-2); LREIMS m / z 91.05 (38.57) [M-C 6 H 11 O 4 ] + , 163.10 (11.34) [M-C 3 H 3 O 3 ] + , 255.20 (0.09) [M + H] + . HT1080 cell and HUVEC were purchased from the Cell Bank of the Chinese Academy of Sciences (Shanghai, China).…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…DIF purified from Laurencia undulata , and demonstrated that it has antioxidant and metal matrix protease inhibitory activity in our previous study. , DIF: 1 H NMR (400 MHz, DMSO- d 6 ) δ H 3.47 (6H, m, H-1′,H-3′, H-6), 3.76 (1H, t, J = 2.6 Hz, H-5), 3.69 (1H, brs, H-2), 3.51 (2H, m, H-3, H-4), 3.41 (1H, m, H-2′), 4.35 (1H, m, HO-2), 4.47 (1H, m, HO-2′), 4.81 (1H, d, J = 2.6 Hz, H-1), 4.56 (1H, m, HO-4), 4.58 (1H, m, HO-6), 4.44 (1H, m, HO-1′), 4.38 (1H, m, HO-3); 13 C NMR (100 MHz, DMSO- d 6 ) δ C 68.9 (C-4), 60.6 (C-1′), 80.6 (C-2′), 71.3 (C-5), 99.4 (C-1), 69.7 (C-3), 61.0 (C-6), 60.8 (C-3′), 68.8 (C-2); LREIMS m / z 91.05 (38.57) [M-C 6 H 11 O 4 ] + , 163.10 (11.34) [M-C 3 H 3 O 3 ] + , 255.20 (0.09) [M + H] + . HT1080 cell and HUVEC were purchased from the Cell Bank of the Chinese Academy of Sciences (Shanghai, China).…”
Section: Methodsmentioning
confidence: 86%
“…Floridoside is one of the main products of carbon fixation in the process of photosynthesis, and can be used as a precursor of cell wall polysaccharides . Previous studies have shown that DIF has the effect of inhibiting liver cell damage caused by alcoholic oxidative stress and the activity of MMP-2 and MMP-9. , In addition, substances with good antioxidant activity have a certain potential for antitumor activity. , Therefore, this study used DIF as the experimental material to study the effect of DIF on tumor cell invasion, metastasis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary antibody (dilution ratio of 1: 2,000) was incubated for 2 h and then washed with TBST three times. Protein expression levels were detected by using enhanced chemiluminescence substrates ( Yang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the production of reactive oxygen species (ROS) during alcohol metabolism, the liver is vulnerable to oxidative stress-induced injury [ 5 ]. Oxidative stress induced by free radicals has been reported to play a key role in the degeneration, inflammation, apoptosis, and necrosis of hepatocytes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%